Association of dietary patterns with socio-demographic, lifestyle, weight status and biochemical profiles among type 2 diabetes mellitus patients in a special Medical Center, Tehran Iran - Zad, Nasrin Darani (2012)
A cross-sectional study was conducted to determine the dietary patterns and their association with socio-demography, lifestyle, weight status and biochemical profiles among type 2 diabetes mellitus subjects and to determine the significant predictors of dietary patterns. Three hundred subjects aged 30 years and above with type 2 diabetes mellitus were selected for this study. Height, weight, and waist circumference were measured and body mass index and waist hip ratio calculated. Biochemical profiles were investigated from past medical history records including glycosylated hemoglobin, fasting blood glucose, postprandial blood glucose, triglycerides, total cholesterol, low and high density lipoprotein cholesterol. For each subject, a physical activity level in weekly metabolic equivalent hours were calculated using International Physical Activity Questionnaire. To measure the dietary intake of the subjects, a semi-quantitative food frequency questionnaire consisting 105 food items was used. The subjects were interviewed on how often they had consumed each of the food items throughout the preceding month to the study period. The frequency intake per day was obtained from the amount of food that was intake each day. The portion sizes of food were estimated to gram with using household measurements. Total energy intake was calculated by summing up energy intake from all foods. Because of the large number of the food items relative to the number of participants, each food was assigned item into 1 of 23 defined food groups. The basis for placing a food item in a certain food group was the similarity of nutrients. Some food items were considered individually as a food group because their nutrient profiles were unique (e.g., eggs, and tea). Three factors (dietary patterns) were identified using factor analysis. Factor 1 was characterized by higher intake of fruit, fish, poultry, low fat dairy, green leafy vegetables, tomato, yellow vegetables, other vegetables, and olive oil and was labeled as vegetables and poultry dietary pattern, Factor 2 was labeled as western dietary pattern which was heavily loaded with legumes, sweets, egg, fish, high fat dairy product, French fries, potatoes, pizza, yellow vegetables. Factor 3 was labeled as mixed dietary pattern with high intake of refined grain, fruits, nuts, tea, whole grains, red meat and olive. Using the multivariate regression model, the factors which contribute significantly to vegetable and poultry dietary pattern in diabetic patients were waist circumference (b=-0.022, p=0.000), low physical activity (b= -0.377, p=0.01), male (b= -0.295, p=0.01), total energy (b=0.001, p=0.000), and body mass index (b= -0.032, p=0.02). The significant factors accounted in the western dietary pattern as moderate physical activity (b= 0.773, p=0.000), male (b=0.436, p=0.001), total cholesterol (b= 0.003, p=0.008), total energy (b=0.000, p=0.001), non-smoker (b= 0.621, p=0.002),uneducated (b= -0.371, p=0.02), single (b= -0.775, p=0.005), fasting blood glucose (b=0.002, p=0.013). In addition, the results, related to mixed dietary pattern, showed that family history of diabetes mellitus (b=0.349, p=0.003), total energy (b=0.001, p=0.000) and high density lipoprotein cholesterol (b=0.01, p=0.002), moderate physical activity (b=-0.39, p=0.03), waist circumference (b=-0.02, p=0.001), body mass index (b=0.03, p=0.01) as well as low density lipoprotein cholesterol (b=-0.003, p=0.04) were significantly associated with mixed dietary pattern. As a conclusion, these findings showed that dietary patterns are influenced by interrelated factors such as socio-cultural, demographic, and lifestyle, which may be important for designing public health nutrition policy and preventive nutrition intervention programs to tackle further diabetes complications among Iranians.